RELATIONSHIPS AMONG WRITING AND READING AS RESPOND ON CRITICAL JOURNAL REVIEW - Dita Grace (IJET (Indonesian Journal of English Teaching), 2018)
AbstractThe integrating of reading and reading in L2 is not the new area, however, the reading and writing only a few studies receives enough attention and implemented in the teaching L1 and L2. This study is aimed to reveal relationships among reading and writing on critical review journal. Thus, the participants in criticism show the ability of L2 learners on reading which confesses through writing. In another occasion, the participants show judgment which representative error is written after reading. This research is going to certain faultiness on writing L2 as judgmental on reading a review on journal.